E-KONSELING SISWA PADA SEKOLAH SMA N 4 PARIAMAN - Najmi, Laila; Hutabri, Elbert; Pratama, Ade (STKIP PGRI Sumatera Barat, 2019)
SMA N 4 Pariaman currently there are obstacles in the processing of student discipline violation scores and consultation issues between parents of students with counseling (BK) and teachers. In this case will be built a system E-Counseling student application website-based system, that can assist the BK in the processing of student discipline violation scores, as well as facilitate teachers and parents in consultation discipline students in school. This system is built using Unified Modeling Language (UML) method which is object oriented software development method using PHP programming language and MySQL database and data collection technique by observation and literature study. This study aims to provide convenience for the BK, teachers and parents to improve discipline in students